There Was a Pole, a Pole, a Pole and a Shame - Adamiec, Joanna (To Tell the History: Polish Contemporary Dramaturgy after 2006, 2023)
The aim of this article is to pay attention to shame as a key affect in the reception of the performance "There was a Pole, Pole, Pole and a Devil…" by Monika Strzępka and Paweł Demirski. The article investigates what shame is, what is its genesis, types and how the mechanism of making viewers feel ashamed or embarrassed affects the perception of the performance. In article there are examples of emotions akin to shame. It wonders if there are topics that all (or almost all) Poles are ashamed of. In that context author examines the role of the city in which the performance was created against the background of the presented events on the issue of provinces. The article triggers the concept of 'shame pedagogy’. Finally, it proves that shame can be an inclusive, community-creative tool and experiencing a moment of deep embarrassment can have a purifying effect on viewers. Thus, it indicates the positive power of shame that encourages reflection and action.